2008
DOI: 10.1097/rhu.0b013e3181776bde
|View full text |Cite
|
Sign up to set email alerts
|

Behçet Disease Associated With Myelodysplastic Syndrome

Abstract: There have been 22 reported cases of Behçet disease associated with myelodysplastic syndrome. The majority of cases belong to incomplete types of Behçet disease and the refractory anemia subtype of myelodysplastic syndrome. We describe a case of a 49-year-old woman with Behçet disease who developed myelodysplastic syndrome with abnormal karyotype-trisomy 8. This change was not due to immunosuppressive agents because her Behçet disease was not treated with these drugs before the onset of myelodysplastic syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Kimura et al [18], having analyzed 46 MDS patients, revealed that trisomy 8 was the risk factor causing the development of multiple ulcerative lesions in intestines and thrombosis in MDS patients. Later, this assumption was confirmed by other researchers as well [19][20][21][22].…”
Section: Discussionsupporting
confidence: 76%
“…Kimura et al [18], having analyzed 46 MDS patients, revealed that trisomy 8 was the risk factor causing the development of multiple ulcerative lesions in intestines and thrombosis in MDS patients. Later, this assumption was confirmed by other researchers as well [19][20][21][22].…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the prevalence rate of trisomy 8 is as high as 73.7% in MDS patients with BD [13]. Previous reports revealed several clinical characteristics such as a low prevalence rate of eye lesions and a high prevalence rate of intestinal lesions in BD patients with MDS involving trisomy 8 [14].…”
Section: Discussionmentioning
confidence: 99%
“…plications associated with BD. This knowledge does not seem to be well-known to dermatologists; therefore, we searched Pubmed for similar cases and found 31 reported cases (1,2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) (Table I). When the BD diagnostic criteria derived from the International Study Group (16) were applied to these 31 cases, recurrent oral aphthae and recurrent genital aphthae were found in more than 70% of the cases; however, ocular lesions were only rarely detected.…”
Section: Discussionmentioning
confidence: 99%